Investigation of the Gracilaria gracilis (Gracilariales, Rhodophyta) proteome response to nitrogen limitation. Issue 3 (28th April 2016) - Naidoo, Rene K.; Rafudeen, Muhammad S.; Coyne, Vernon E.
Abstract : Inorganic nitrogen has been identified as the major growth‐limiting nutritional factor affecting Gracilaria gracilis populations in South Africa. Although the physiological mechanisms implemented by G. gracilis for adaption to low nitrogen environments have been investigated, little is known about the molecular mechanisms of these adaptions. This study provides the first investigation of G. gracilis proteome changes in response to nitrogen limitation and subsequent recovery. A differential proteomics approach employing two‐dimensional gel electrophoresis and liquid chromatography–tandem mass spectrometry was used to investigate G. gracilis proteome changes in response to nitrogen limitation and recovery. The putative identity of 22 proteins that changed significantly ( P  < 0.05) in abundance in response to nitrogen limitation and recovery was determined. The identified proteins function in a range of biological processes including glycolysis, photosynthesis, ATP synthesis, galactose metabolism, protein‐refolding and biosynthesis, nitrogen metabolism and cytoskeleton remodeling. The identity of fructose 1, 6 biphosphate (FBP) aldolase was confirmed by western blot analysis and the decreased abundance of FBP aldolase observed with two‐dimensional gel electrophoresis was validated by enzyme assays and western blots. The identification of key proteins and pathways involved in the G. gracilis nitrogen stress response provide a better understanding of G. gracilis proteome responses to varying degrees of nitrogen limitation and is the first step in the identification of biomarkers for monitoring the nitrogen status of cultivated G. gracilis populations.